Treatment of skeletal class III malocclusions with a combination of orthodontic treatment and orthognathic surgery - Habar, Eddy H.; Ruslin, Muhammad (Hasanuddin University, 2020)
Purpose: This article discusses a case reports of skeletal class III malocclusions treated with fixed orthodontic appliances and orthognathic surgery. Methods: Female patients aged 16 with complaints of crossbite in the anterior region and facial aesthetics. The objective examination showed ectostem teeth at 13, peg shaped teeth at 12, agenesi at 22 and diastema in teeth 34-35. The mandible Â looks forward. Results: Orthodontic treatment with fixed orthodontic appliances to straighten teeth in the dental arch then orthognathic surgery was performed to correct advanced of mandibularÂ jaw. Conclusions: Maximum results are obtained by interdisciplinary treatment between orthodontist and oral surgeon.